2015
DOI: 10.1039/c5ta02486b
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism from quantum molecular dynamics for the initial thermal decomposition of 2,4,6-triamino-1,3,5-triazine-1,3,5-trioxide (MTO) and 2,4,6-trinitro-1,3,5-triazine-1,3,5-trioxide (MTO3N), promising green energetic materials

Abstract: A variety of initial reactions are favorable for MTO and MTO3N, two possible candidates for green energetic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…25 Then we studied the initial reaction mechanisms for thermal decomposition using quantum mechanics dynamics simulations. 26 These simulations suggested that MTO3N would have good thermal stability while MTO would exhibit intermolecular hydrogen transfer processes that might lead to higher sensitivity. 26 In this paper we predict the performance of MTO and MTO3N by using ReaxFF Reactive Molecular Dynamics (ReaxFF-RxMD) to predict the Chapman-Jouguet state of a sustaining detonation wave.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…25 Then we studied the initial reaction mechanisms for thermal decomposition using quantum mechanics dynamics simulations. 26 These simulations suggested that MTO3N would have good thermal stability while MTO would exhibit intermolecular hydrogen transfer processes that might lead to higher sensitivity. 26 In this paper we predict the performance of MTO and MTO3N by using ReaxFF Reactive Molecular Dynamics (ReaxFF-RxMD) to predict the Chapman-Jouguet state of a sustaining detonation wave.…”
Section: Introductionmentioning
confidence: 95%
“…26 These simulations suggested that MTO3N would have good thermal stability while MTO would exhibit intermolecular hydrogen transfer processes that might lead to higher sensitivity. 26 In this paper we predict the performance of MTO and MTO3N by using ReaxFF Reactive Molecular Dynamics (ReaxFF-RxMD) to predict the Chapman-Jouguet state of a sustaining detonation wave. Here the detonation products are predicted directly from the reactive dynamics simulation of the complex chemical reactions starting from initial reactant to the thermodynamic conditions of the CJ state, with no assumptions about composition of the products.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, we have also used the crystal structures predicted in this paper to study the thermal decomposition of MTO and MTO3N using ab initio quantum mechanics molecular dynamics (QMMD) methods. 14 These high level QM calculations showed that the proposed MTO and MTO3N materials should have excellent performance; however, we found that MTO should be more sensitive than MTO3N because it undergoes a simultaneous two proton transfer at modest temperature or pressure. This shows the value of the structures reported herein and the importance of having a practical methodology for crystal structure prediction, which is the focus of the current paper.…”
Section: Introductionmentioning
confidence: 69%